2004
DOI: 10.4049/jimmunol.173.1.666
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Invasion-Inhibitory Antibodies Specific for the 19-kDa Fragment of Merozoite Surface Protein-1 (MSP-119) Can Play a Protective Role against Blood-Stage Plasmodium falciparum Infection in Individuals in a Malaria Endemic Area of Africa

Abstract: The C-terminal 19-kDa fragment of Plasmodium falciparum merozoite surface protein-1 (MSP-119) is a target of protective Abs against blood-stage infection and a leading candidate for inclusion in a human malaria vaccine. However, the precise role, relative importance, and mechanism of action of Abs that target this protein remain unclear. To examine the potential protective role of Abs to MSP-119 in individuals naturally exposed to malaria, we conducted a treatment time to infection study over a 10-wk period in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
157
3
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(175 citation statements)
references
References 49 publications
(48 reference statements)
11
157
3
3
Order By: Relevance
“…However, antibodies measured by ELISA cannot be relied on as a direct measure of functional immunity, as we found no clear or consistent association between antibodies by ELISA and differences in inhibitory activity between comparison lines. Consistent with this, prior studies reported no correlation between antibodies against MSP1 19 by ELISA and MSP1 19 -specific inhibitory antibodies (46). In other studies we have found antibodies against other merozoite antigens measured by ELISA to be poor predictors of inhibitory activity (F. McCallum, K. Persson, D. Wilson, and J. Beeson, unpublished observations).…”
Section: Figuresupporting
confidence: 75%
“…However, antibodies measured by ELISA cannot be relied on as a direct measure of functional immunity, as we found no clear or consistent association between antibodies by ELISA and differences in inhibitory activity between comparison lines. Consistent with this, prior studies reported no correlation between antibodies against MSP1 19 by ELISA and MSP1 19 -specific inhibitory antibodies (46). In other studies we have found antibodies against other merozoite antigens measured by ELISA to be poor predictors of inhibitory activity (F. McCallum, K. Persson, D. Wilson, and J. Beeson, unpublished observations).…”
Section: Figuresupporting
confidence: 75%
“…However, it remains unknown whether all antibodies to PfMSP-1 19 detected by ELISA are functionally relevant. A recent cohort study in Western Kenya suggested that the ability of naturally acquired antiPfMSP-1 19 antibodies to inhibit merozoite invasion in vitro may be a better correlate of clinical immunity to malaria than the mere presence of antibodies measured by conventional ELISA (John et al 2004). Contrasting with the extensive investigation of the role of Pf MSP-1 19 in naturally acquired immunity, little is known about the immune recognition of the ortholog protein of P. vivax (Pv).…”
mentioning
confidence: 97%
“…The results demonstrated that the invasion inhibitory antibodies were specific for the C-terminal MSP-1p19 (John et al, 2004). Overall, there was a lack of association of total IgG or IgG subclass Abs to MSP-1p19 measured by ELISA with either invasion-inhibitory activity or protection against infection.…”
Section: The Role Of Msp-1 In Natural Immunitymentioning
confidence: 79%
“…Serological studies have provided significant evidence suggesting that immune responses directed against the C-terminus of MSP-1 (MSP-1p19 and MSP-1p42) are associated with immunity in preclinical models (Long et al, 1994;Egan et al, 1999;Darko et al, 2005;Parkkinen et al, 2006). Moreover, protective immunity as defined by lower mortality and morbidity of individuals residing in endemic areas was also associated with MSP-1p19 (Egan et al, 1999;John et al, 2004).…”
Section: Msp-1 and Its Role In Immunity And Infectionmentioning
confidence: 99%